Animation 1 : learn to animate step by step 2026-02-16T05:26:58+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Blair, Preston (How to draw & paint, 2019)

(untitled)
"... covers the most important aspects of cartooning, such as working out layouts, planning scenes, and synchronizing mouth action. It also provides instruction on drawing a variety of believable animated characters, with tips on using lines of action to create realistic motion." --back cover